Influence of Occupational Stress on Work Engagement among Nigerian Library Personnel - Chiedu Eseadi; Charity Neejide Onyishi; Osita Victor Ossai (Journal An-Nafs: Kajian Penelitian Psikologi, 2022)
The study examined occupational stress and job engagement among library personnel at selected Nigerian state and federal universities. A descriptive survey methodology was employed in the study. This study used questionnaires for ascertaining work engagement and occupational stress to survey 76 respondents. Results indicated that library personnel experienced high occupational stress, which displayed significantly low levels of job engagement. In contrast, those with a low level of occupational stress showed significantly increased levels of engagement at work. The data suggested that female library personnel reported experiencing more occupational stress than male library personnel and the mean difference was statistically significant, t (74) = -3.416, p =.001. The limitation of this research includes the smallness of sample size, which calls for a larger sample to validate the findings further. Rational emotive behavioral therapy can be adapted for managing the levels of work engagement and occupational stress in librarians.